Проза второй половины XIX века: [сборник] / сост. Д. П. Бак ; худож. В. В. Медведев - Бак Дмитрий (Пушкинская библиотека, 2001)
Экземпляры: (20181106) / Инвентарный номер: 1809 / Цена: / Сис.шифр: 84(2Рос=Рус)1 / Авт.знак: П 79 / ББК: 84(2Рос=Рус)1-4